ANALISIS TINGKAT KEBAHAGIAAN PADA LANSIA PENERIMA MANFAAT DAN BUKAN PENERIMA MANFAAT PROGRAM DAY CARE SERVICE - Rakhmadani, Nur Anna; Sutria, Eny; Hafid, Muhammad Anwar (Journal of Islamic Nursing, 2019)
Considering the importance of providing services for the elderly, the social institution Tresna Werdha also manages the day care service program, where this service is very helpful for the elderly who need services to create social relationships. Services provided through day care services are social services, physical services, psychosocial services, skills services, spiritual and religious services and providing economic business assistance. This service is an activity to increase productivity in order to increase income and as a place or facility for positive activities in the utilization of leisure time for the elderly.Research design is descriptive with a sample of 88 people using purposive sampling divided into two groups, namely 44 elderly people in each group. Data collection techniques using oxford happiness questionnaire sheet while the analysis used with Mann Whitney Test (alpha 0.05)Based on the results of the study, it was found that there were differences in happiness levels in elderly beneficiaries and not beneficiaries of day care service programs (p = 0,000). Elderly beneficiaries of the dominant day care service program have a high level of happiness as evidenced by the number of elderly in the category of high happiness 37 people (84.1%) compared to the elderly who did not receive the benefits of the day care service program as evidenced by the number of 26 people (59.1%) . Elders who attend their day care service get family support and services from social care institutions in the form of physical, skills, psychosocial, spiritual and religious services and can meet with peers. Keywords: Elderly Happiness, Day Care Service